ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN BERBASIS METAVERSE MENGGUNAKAN SPATIAL.IO PADA MATERI KERJA SAMA MULTILATERAL KELAS VI SEKOLAH DASAR - Ade Lia Agustina; Harini, Bunda; Dewi Maharani, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The Merdeka Curriculum emphasizes the need for interactive and contextual learning, including in the topic of multilateral cooperation within the Grade VI IPAS subject. However, classroom practices still rely heavily on traditional approaches that are less effective in supporting students’ understanding of global concepts in an engaging and interactive manner. This condition highlights the need for digital technology integration, particularly the Metaverse, which offers a three-dimensional learning environment that enables immersive learner interaction. This study aims to analyze the need for developing Metaverse-based learning media for Grade VI students at SDN 11 Indralaya. A descriptive qualitative method was employed, utilizing interviews, observations, and documentation. Data were analyzed through triangulation to obtain an objective overview of student characteristics and learning conditions. The findings indicate that learning activities remain centered on textbooks and teacher explanations, while available technological facilities are not yet optimally used. Students tend to have audio-visual learning preferences and show strong interest in digital media that provide richer visualization and interaction. The teacher also recognizes the necessity for innovative media to enhance learning engagement. These findings suggest that Metaverse platforms such as Spatial.io have great potential to be implemented as learning media that enrich the learning experience and support the understanding of multilateral cooperation. This study serves as a foundational reference for developing Metaverse-based learning media using Spatial.io for Grade VI students in alignment with their learning needs and 21st-century educational demands.